Eosinophilic gastroenteritis in an 18-year-old male with prolonged nephrotic syndrome - Da Min Choi; Jung Eun Pyun; Hyung Eun Yim; Kee Hwan Yoo; Jung Ok Shim; Eun Jung Lee; Nam Hee Won (Korean Pediatric Society, 2016)
Eosinophilic gastroenteritis is a rare disease characterized by prominent eosinophilic tissue infiltration of the gastrointestinal tract. Here, we report a case of eosinophilic gastroenteritis in an 18-year-old patient with prolonged nephrotic syndrome who presented with abdominal pain and peripheral hypereosinophilia. During the previous 2 years, he had visited local Emergency Department several times because of epigastric pain and nausea. He had been treated with steroid-dependent nephrotic syndrome since 3 years of age. Tests ruled out allergic and parasitic disease etiologies. Gastroduodenoscopy with biopsy revealed marked eosinophilic infiltration in the duodenum. Renal biopsy findings indicated minimal change disease spectrum without eosinophilic infiltration. The oral deflazacort dosage was increased, and the patient was discharged after abdominal pain resolved. To our knowledge, this is the first report of eosinophilic gastroenteritis in a patient with minimal change disease.